The Role of Organizational and Cultural Factors in the Adoption of Activity-Based Costing: The Case of Moroccan Firms - Karim Charaf; Pierre-Laurent Bescos (Journal of Accounting and Management Information Systems (JAMIS), 2013)
The purpose of this study has been to measure the adoption of Activity-Based Costing (ABC) by Moroccan companies, and to identify the characteristics and causes of its implementation. Employing a survey methodology, a questionnaire was used to collect data on the organizational and cultural factors meant supposed to facilitate the adoption of ABC by companies. To obtain rich data, three semi-structured interviews were carried out. The results indicate that the emphasis on the cost information and cultural factors explain the adoption. A comparison is possible with other international studies and can show the contributions and limitations of our results.
Keywords: M41; M21; 650; Activity-Based Costing; ABC; Adoption; Culture; Morocco